MFAP4 Deficiency Attenuates Angiotensin II-Induced Abdominal Aortic Aneurysm Formation Through Regulation of Macrophage Infiltration and Activity - Pilecki, Bartosz; de Carvalho, Paulo V. S. D.; Kirketerp-Møller, Katrine L.; Schlosser, Anders; Kejling, Karin; Dubik, Magdalena; Madsen, Nicklas P.; Stubbe, Jane; Hansen, Pernille B. L.; Andersen, Thomas L.; Moeller, Jesper B.; Marcussen, Niels; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objective: Abdominal aortic aneurysm (AAA) is a common age-related vascular disease characterized by progressive weakening and dilatation of the aortic wall. Microfibrillar-associated protein 4 (MFAP4) is an extracellular matrix (ECM) protein involved in the induction of vascular remodeling. This study aimed to investigate if MFAP4 facilitates the development of AAA and characterize the underlying MFAP4-mediated mechanisms. Approach and Results: Double apolipoprotein E- and Mfap4-deficient (ApoE−/−Mfap4−/−) and control apolipoprotein E-deficient (ApoE−/−) mice were infused subcutaneously with angiotensin II (Ang II) for 28 days. Mfap4 expression was localized within the adventitial and medial layers and was upregulated after Ang II treatment. While Ang II-induced blood pressure increase was independent of Mfap4 genotype, ApoE−/−Mfap4−/− mice exhibited significantly lower AAA incidence and reduced maximal aortic diameter compared to ApoE−/− littermates. The ApoE−/−Mfap4−/− AAAs were further characterized by reduced macrophage infiltration, matrix metalloproteinase (MMP)-2 and MMP-9 activity, proliferative activity, collagen content, and elastic membrane disruption. MFAP4 deficiency also attenuated activation of integrin- and TGF-β-related signaling within the adventitial layer of AAA tissues. Finally, MFAP4 stimulation promoted human monocyte migration and significantly upregulated MMP-9 activity in macrophage-like THP-1 cells. Conclusion: This study demonstrates that MFAP4 induces macrophage-rich inflammation, MMP activity, and maladaptive remodeling of the ECM within the vessel wall, leading to an acceleration of AAA development and progression. Collectively, our findings suggest that MFAP4 is an essential aggravator of AAA pathology that acts through regulation of monocyte influx and MMP production.